Brain Network Associated with Three Types of Remote Associations: Graph Theory Analysis. Issue 3 (3rd July 2022) - Wu, Ching-Lin
ABSTRACT: Remote association, the ability to form new relations between independent elements, was assessed using the Remote Associates Test (RAT). The Chinese RAT (CRAT) includes the Chinese radical RAT (CRRAT), Chinese word RAT (CWRAT), and Chinese compound RAT (CCRAT). Behavioral research indicates that an individual's performance on the CRAT reflects different ways of remote associations, although there are few studies on brain networks. Therefore, this study analyzed the correlation between structural network connectivity and CRAT performance in 52 adults. The findings showed that CCRAT performance had a positive correlation with clustering coefficients, local efficiency, and global efficiency, but a negative correlation with the characteristic path length. CWRAT performance was positively correlated with normalized clustering coefficients and small-world-ness, and CRRAT performance was positively correlated with characteristic path length. This study enriches our understanding of the process of remote association by exploring different remote associations from a brain network perspective.